Civil Society in Development: How Platform Groups Politicized EPA Negotiation between EU and West Africa (Global Journal of Human-Social Science, 2019)
The core trajectory of this essay is to explore further the transformative power of civil society as advanced in by neo-Gramscian scholars by looking closely at how platform civil society groups organized in transnational networks politicized the Economic Partnership Agreement (EPA) negotiation process between the EU and West Africa. The paper argued that platform groups politicized the EPA negotiation process by drawing attention to the potential development implications of concluding EPA with the EU for West Africa in particular and African, Caribbean, and Pacific (ACP) regions in general. Two questions are raised in the paper, the first of which addressed why platform civil society groups in West Africa contested the EPA. The second question engaged with how platform groups organized and mobilized action across national borders and regional divide for this purpose. The paper argued that platform groups in West Africa became resistant to EPA and organized mainly to block its ratification because EPAs are generally perceived to have a neoliberal undertone that potentially challenges African, Caribbean and Pacific (ACP) countries' prospects for socioeconomic development.
Keywords: civil society; EPA; transnational civil society; agency; counter-hegemony